The Use of Reductive Methylation of Lysine Residues to Study Protein-Protein Interactions in High Molecular Weight Complexes by Solution NMR - Lee, Youngshim; Abraham, Sherwin J.; Gaponenko, Vadim (IntechOpen, 2012)
None